The effectiveness of an educational unit to develop students’ skills in designing fashion shows using virtual reality and its impact on electronic shopping in Asir region, Saudi Arabia - Elkherbaway, Randa Mounir; Kanona, Samar Ahmed; Bosiala, Ngawha Kamel (Arab Journal for Sciences and Research Publishing, 2023)
The aim of the research is to measure the effectiveness of an educational unit to develop students’ skills in designing fashion shows using three-dimensional design programs and its impact on electronic shopping, using various three-dimensional design programs by preparing an educational unit to develop students’ skills in designing fashion shows using virtual reality for students of King Khalid University. Within the course of fashion shows and the extent of the effectiveness of the proposed educational unit on the skill and cognitive performance of female students in designing and preparing a virtual fashion show and its impact on online shopping for fashion in the Asir region, Saudi Arabia, The research sample consisted of (86) female students in the Department of Fashion Design- College of Home Economics- at King Khalid University in the Kingdom of Saudi Arabia. The study concluded that the hypotheses of the study were fulfilled, as the first hypothesis was fulfilled, as there are statistically significant differences between the average scores of female students in the knowledge and skills included in the proposed unit in the pre and post applications in favor of the post application, and the second hypothesis was achieved, as there are statistically significant differences between the average scores of female students in the cognitive test before applying The unit and after it in favor of the post application, and the third hypothesis was verified, as there are statistically significant differences between the mean scores of the students in the skill test before and after the application of the unit in favor of the post application. The research recommended the necessity of expanding the study of virtual reality because of its very large positive impact on the success of electronic shopping and focusing on open teaching methods such as digital technology, social media sites and brainstorming, and working with the group system in teaching because of its impact on improving creative thinking among students.